Fractal impeller for stirred tank reactors - Kulkarni, Amol A.; Jha, Neha; Singh, Abhishek; Bhatnagar, Sumit; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2011)
Stirred tank reactors are used for variety of applications at different scales of operation. The conventional impellers tend to develop regions having nonuniform energy dissipation rates in the stirred reactor. In this work, we propose a novel fractal impeller, which helps in reducing such nonuniformities and help develop a uniform randomness throughout the reactor. The impeller geometry is discussed in detail. Experimental measurements of the power consumption, mixing time, suspension quality, and the ability for gas dispersion were carried out, and the performance is compared with the conventional impellers. The impeller is seen to have a low power number, and it can generate a uniform suspension of particles even at relatively lower impeller speeds and can efficiently disperse gas into liquid to yield relatively higher gas hold-up values. The Fourier analysis of the power consumption time series data indicates that no specific prominent frequency events exist in the reactor, and the spectrum showed several frequency events to exist in the reactor with almost identical prominence.

Improvement in oxygen evolution performance of NiFe layered double hydroxide grown in the presence of 1T-Rich MoS2 - Chakraborty, Soumita; Marappa, Shivanna; Agarwal, Sakshi; Bagchi, Debabrata; Rao, Ankit; Vinod, Chathakudath P.; Peter, Sebastian C.; Singh, Abhishek; Eswaramoorthy, Muthusamy (ACS Applied Materials & Interfaces, 2022)
NiFe layered double hydroxide (NiFe LDH) grown in the presence of MoS2 (rich in 1T phase) shows exceptional performance metrics for alkaline oxygen evolution reaction (OER) in this class of composites. The as-prepared NiFe LDH/MoS2 composite (abbreviated as MNF) exhibits a low overpotential (eta(10)) of 190 mV; a low Tafel slope of 31 mV dec(-1); and more importantly, a high stability in its performance manifested by the delivery of current output for 45 h. It is important to note that this could be achieved with an exceedingly low loading of 0.14 mg cm(-2). The mass activity of this composite (97 A g(-1)) is about 14 times greater than that of the conventional RuO2 (7 A g(-1) ) at eta = 200 mV. When normalized with respect to the total metal content, a mass activity of 1000 A g(-1) (eta = 300 mV) was achieved. Impedance analysis further reveals that the significant reduction in charge-transfer resistance and hence high current density (5 times greater as compared to NiFe LDH at eta = 300 mV) observed for MNF is associated with interfacial adsorption kinetics of intermediates (R-1). Significant enhancement in the intrinsic activity of MNF over LDH has been observed through normalization of current with the electrochemically active surface area. Computational studies suggest that the Ni centers in the composite act as the active sites for OER, which is well-corroborated with the observed postreaction appearance of Ni3+ species.
Keywords: Impedance; LDH-MoS2 hybrid electrocatalyst; mass activity; OER; overpotential